Asthma and Food Allergy in Children: Is There a Connection or Interaction? - Caffarelli, Carlo; Garrubba, Marilena; Greco, Chiara; Mastrorilli, Carla; Povesi Dascola, Carlotta (Frontiers in Pediatrics, 2016)
This review explores the relationship between food allergy and asthma. They can share the same risk factors, such as parental allergy, atopic eczema and allergen sensitization and they often coincide in the same child. Coexistence may negatively influence the severity of both conditions. However, it remains to be determined whether food allergy may directly affect asthma control. An early food sensitization in the first year of life can predict the onset of asthma. Furthermore, asthmatic symptoms could rarely be caused by ingestion or inhalation of the offending food. Asthma caused by food allergy is severe and may be associated with anaphylactic symptoms. Therefore, an accurate identification of the offending foods is necessary in order to avoid exposure. Patients should be instructed to treat asthmatic symptoms quickly and to use self-injectable epinephrine.